Perception of respect and maintenance of dignity in hospitalized patients - Campillo, Beatriz; Corbella, Josep; Gelpi, Marta; Martinez, Elisenda; Viciana, Miguel Angel; Montiel, Jose; Abós, Esther; Callejón, Sandra; Alonso, Milagros (Acta Bioethica, 2020)
Dignity is a fundamental concept that can be modified during hospitalization by the behavior of professionals. Despite its importance, there are few instruments to evaluate it. A transversal, descriptive, analytical and quantitative study evaluates the patient’s perception of dignity based on the “Cuestionario de percepción de dignidad de paciente hospitalizado (CuPDPH)” in Spanish and validated. The sample was composed of 148 men and 138 women with an average age of 62.82 (SD 4.05). No significant differences were found in the scores and sociodemographic variables. The results allow us to identify highlights and areas of improvement in the care and respect for the dignity of hospitalized persons. Going deeper into the topic is an opportunity, on the way to professional excellence, defending technical competence and ethical competence.